2011
DOI: 10.3109/03639045.2011.608191
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure-based drug delivery systems for brain targeting

Abstract: This review would give an insight to the researchers working on neurodegenerative and non-neurodegenerative diseases of the CNS including brain tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 271 publications
0
32
0
Order By: Relevance
“…59 Similar enhancement of brain uptake was also observed in other brain-targeted nanocarriers. 35,60 Batrakova et al reported that Pluronic P85 can sensitize multidrug resistant cancer cells 61 and enhance the delivery of P-gp substrates to the brain 26 through a common mechanism: inhibition of P-gp activity. Zhang et al showed that P123 micelles also have the ability to inhibit P-gp and consequently sensitize MDR cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…59 Similar enhancement of brain uptake was also observed in other brain-targeted nanocarriers. 35,60 Batrakova et al reported that Pluronic P85 can sensitize multidrug resistant cancer cells 61 and enhance the delivery of P-gp substrates to the brain 26 through a common mechanism: inhibition of P-gp activity. Zhang et al showed that P123 micelles also have the ability to inhibit P-gp and consequently sensitize MDR cells.…”
mentioning
confidence: 99%
“…In addition, it has been suggested that the polymeric-based nanocarriers enter brain tissues without the irreversible disruption of the BBB. 60 In brain diseases such as epilepsy, the P-gp level is increased to the point that a therapeutic brain concentration cannot be achieved at tolerable drug doses, leading to drug refractoriness. 1 Previous studies have shown that the improved antiepileptic effects of some AEDs can be achieved by increasing their concentrations in epileptogenic focus.…”
mentioning
confidence: 99%
“…17 ) (Beg et al 2011 ;Blasi et al 2011 ;Celia et al 2011 ;De Rosa et al 2012 ;MartinBanderas et al 2011 ;Nair et al 2012 ;Raudino et al 2011 ;Panagiotou and Fisher 2011 ;Crunkhorn 2012 ). In some instances, they contain inorganic cores such as gold or feature coatings of polyethylene glycol or other polymers proposed to enhance delivery (Haque et al 2012 ;Malhotra and Prakash 2011 ;Su et al 2011 ;Wankhede et al 2012 ;Herve et al 2008 ). The drug payload is loaded onto the nanoparticles via non-covalent interactions, meaning that a given nanocarrier system could potentially be deployed to deliver many drugs without modifi cation to the drug or the nanocarrier.…”
Section: Nanocarriersmentioning
confidence: 99%
“…130,131 Many strategies have been developed to overcome the BBB, such as drug delivery systems, liposomes, polymeric and solid lipid NPs (SLNs), solid lipid carriers, liquid crystals (LCs), microemulsions (MEs), and hydrogels. [127][128][129][132][133][134] The physicochemical characteristics of drugs, such as its hydrophilicity or lipophilicity, ionization, high molecular weight, poor bioavailability, extensive metabolization, and adverse effects, can result in its failure as a pharmacotherapeutic. 127,135 These limitations can be overcome by the use of intranasal administration, which offers an alternative, noninvasive means of drug delivery to the brain because drugs delivered this way can bypass the BBB and directly transport drugs to the CNS.…”
mentioning
confidence: 99%
“…114 Nevertheless, the inflammatory pathways in AD 124,125 and treatment with antiinflammatory molecules has the potential to delay, prevent, or treat AD. 125,126 Nanotechnology-based drug delivery systems Treatment options are limited mainly due to the inability of drugs to cross the blood-brain barrier (BBB) [127][128][129] or their poor solubilities by oral route. 130,131 Many strategies have been developed to overcome the BBB, such as drug delivery systems, liposomes, polymeric and solid lipid NPs (SLNs), solid lipid carriers, liquid crystals (LCs), microemulsions (MEs), and hydrogels.…”
mentioning
confidence: 99%